Competitive advantage of hotels in Jinhua Combining Institutional and Resource based Views - Wang, Wei (2007)
This research endeavors to address the sustainable competitive advantage issue of Chinese firms from the paradigm combining resource based and institutional views. Both views have been used extensively in the strategy research literature in China, and the integrative perspective has the potential to approach the strategy issues new insight by incorporating the institutional influence on resource. Establishing on extensive RBV, institutional theory literature and especially Oliver(1997) work on the combination of RBV and institutional theory, this paper proposes a variant integrative conceptual framework.. To investigate the field, I did a detailed qualitative case research in Jinhua City in Zhejiang Province. It was found that the competitive force and institutional force are both strong in hotel industry in Jinhua and the institution did have impact on hotels performance. The 9 sample hotels investigated demonstrated much variance in resources and performance. Analyzed with the proposed framework, it was found that physical resource, financial resource, human resource, relational resource, governance resource and marketing resource have most significant roles in hotels. All of them were shown as valuable and necessary to manage the market and institutional forces, while the human resource and relational resource was argued to be sources of sustainable competitive advantage. In addition, the underlined relationship between resources was proposed. In a word, this research contribute to the understanding of what, how, when and where resources are valuable and sustainable, and it also demonstrates the value of incorporating institutional theory in strategy research.